Effect of Conceptual, Understanding, Procedural, and Problem-Based Learning Models Using a Contextual Approach on Students’ Conceptual Understanding Skills - Tiara Fitriana; Nizlel Huda; Wardi Syafmen (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical conceptual understanding is one of the key competencies that students must possess in mathematics learning, as it enables them to connect concepts, explain procedures, and apply mathematical knowledge in various problem-solving situations. However, in classroom practice, students’ mathematical conceptual understanding remains relatively low, indicating the need for instructional models that can facilitate more meaningful learning. This study was motivated by the low level of mathematical conceptual understanding among seventh-grade students at SMP Negeri 7 Muaro Jambi. It aimed to determine whether the Conceptual Understanding Procedures (CUPs) learning model with a contextual approach and Problem-Based Learning (PBL) with a contextual approach influenced the mathematical conceptual understanding of seventh-grade students at SMP Negeri 7 Muaro Jambi in the 2025/2026 academic year. This study employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The population consisted of all seventh-grade students at SMP Negeri 7 Muaro Jambi during the 2025/2026 academic year, and the sample was selected through simple random sampling. The research instruments included a test of students’ mathematical conceptual understanding and an observation sheet used to assess the implementation of the learning process. The test was administered before and after the instructional treatment. Based on the N-gain analysis followed by a one-way ANOVA, the findings revealed a significant difference in the effects of the CUPs and PBL models with a contextual approach on students’ mathematical conceptual understanding. Further analysis showed that students taught using the CUPs and PBL models achieved significantly different mean scores in mathematical conceptual understanding compared with those taught using the Direct Instruction model.